2014
DOI: 10.1093/ckj/sfu010
|View full text |Cite
|
Sign up to set email alerts
|

How good are we at managing acute kidney injury in hospital?

Abstract: IntroductionAcute kidney injury (AKI) is a common clinical problem associated with adverse outcomes. This study identifies the incidence of AKI in two UK district general hospitals' without on-site renal services and assesses AKI management and level of nephrologist input.MethodsThe AKIN classification was used to identify 1020 AKI patients over 6 months. Data were collated on patient demographics, AKI management and referral to nephrology and intensive care services. Short/long-term renal outcomes were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…In developed counties, it is reported that about 10% of AKI cases have not been recognized by the attending doctors [58], whereas the recently published national survey of AKI in China reveals a dramatic nonrecognition rate of AKI across the country [4]. About 3/4 of the AKI patients had not been recognized by the physicians in charge, and patients coming from less economically developed regions were at a higher risk for underrecognition of AKI.…”
Section: Recognition and Treatment Of Aki In Asiamentioning
confidence: 99%
“…In developed counties, it is reported that about 10% of AKI cases have not been recognized by the attending doctors [58], whereas the recently published national survey of AKI in China reveals a dramatic nonrecognition rate of AKI across the country [4]. About 3/4 of the AKI patients had not been recognized by the physicians in charge, and patients coming from less economically developed regions were at a higher risk for underrecognition of AKI.…”
Section: Recognition and Treatment Of Aki In Asiamentioning
confidence: 99%
“…47,48 Standardized follow-up is important after an episode of AKI and can help to prevent the development of CKD. 49 This area can be addressed quickly and relatively easily because less than50%ofpatientswith the most severe AKI will have a follow-up creatinine level measured within the first 3 months of hospitalization, and followup is even less likely to be obtained after less severe AKI. 50 We acknowledge the limitations of all retrospective studies.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…77 Evaluating acute changes in urine output has important prognostic implications for the severity of AKI as seen by classification of RIFLE criteria. [4][5][6]10 Oliguria is defined as reduction in urine output of less than 500 mL/d, and anuria as less than 50 mL. Furthermore, oliguric ATN has been associated with increased risk of mortality and requirement for renal replacement therapy in comparison to nonoliguric AKI conditions.…”
Section: History and Clinical Evaluationmentioning
confidence: 99%
“…[4][5][6][7][8][9] More importantly, the development of AKI is independently associated with high mortality rates, increased length of stay, and risk of developing permanent chronic kidney disease (CKD). [4][5][6][7][9][10][11] …”
mentioning
confidence: 99%